2012
DOI: 10.1007/s12119-012-9162-1
|View full text |Cite
|
Sign up to set email alerts
|

Love as a Fictitious Commodity: Gift-for-Sex Barters as Contractual Carriers of Intimacy

Abstract: Gift-for-sex (GFS) barters are a niche practice potentially representing the commodification of everyday dating practices. We inquire how GFS exchanges are practiced and understood in contemporary Russia. Second, we situate these in relation to contemporary economic culture. Our project provides answers in two steps based on online content. First, we identify GFS exchange practices within a major dating website. Next, we take the signals exchanged in those dating profiles and display their intersubjective mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Overall, I found that sugar arrangements comprise a unique relational package with their own subcultural and interpersonal scripts that, in the majority of cases, differ from prostitution. My findings echo the sentiments of other researchers who also argue that sugar relationships are distinct from commercial sex work (Cheung et al 2016; Hunter 2002; Nayer 2017; Swader et al 2013; Swader and Vorobeva 2015; Swindler and Watkins 2007). For instance, based on their study of male benefactors who engage in compensated dating, Cassini Sai Kwan Chu and Karen Joe Laidler (2016) note that compensated dating differs from prostitution in that it is “.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Overall, I found that sugar arrangements comprise a unique relational package with their own subcultural and interpersonal scripts that, in the majority of cases, differ from prostitution. My findings echo the sentiments of other researchers who also argue that sugar relationships are distinct from commercial sex work (Cheung et al 2016; Hunter 2002; Nayer 2017; Swader et al 2013; Swader and Vorobeva 2015; Swindler and Watkins 2007). For instance, based on their study of male benefactors who engage in compensated dating, Cassini Sai Kwan Chu and Karen Joe Laidler (2016) note that compensated dating differs from prostitution in that it is “.…”
Section: Discussionsupporting
confidence: 84%
“…Although some female prostitutes may develop a genuine liking for their clients (Albert 2001; Sanders 2008), the script that typically guides their interactions does not dictate that they develop and maintain authentic emotions for customers. This, in part, is what distinguishes a “benefactor” from a “client” (Swader et al 2013:613), as legally speaking, engaging in sexual activity with a person for whom an individual has no emotion for the sole purpose of profit is considered prostitution (Motyl 2013). Fifth, although the subcultural sugar relationship script called for sugar partners to maintain arrangements that were NSA, the lives of recipients and benefactors were more intertwined than what is described in the literature on prostitution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Problems with our questions were quickly revealed when we piloted the survey in Vilnius among the agency representatives and later when the survey was administered to clients. For example, we knew that agencies were recruiting women known by staff to engage in sex exchange broadly defined (for example, both women who identified as sex workers and those who engaged in ‘compensated dating’ (Swader and Vorobeva 2015; Swader, Strelkova, and Sutormina 2013)). However, we were getting extremely low response rates to the questions about women’s experience with sex exchange.…”
Section: Introductionmentioning
confidence: 99%